Prestack spectral blueing: A tool for increasing seismic resolution - Kazemeini, S.; Fomel, S.; Juhlin, Christopher (2008)
It has been shown that boosting the more greatly attenuated higher frequencies (blue part) within the seismic band in order to match well-log-derived reflectivity can improve the resolution of seismic data. This method, known as spectral blueing includes designing and applying one or several operators to post-stack seismic data in order to enhance attenuated high frequencies within the frequency band. In this study we show that applying the blueing operator to prestack data also improves seismic resolution and may produce more consistent results and cause fewer ringing artifacts. Prestack blueing, poststack blueing and no blueing results are compared. 3D seismic data from the Ketzin CO2 sequestration site are used to illustrate this method.